Interferencje leksykalne w języku najstarszych mieszkańców małego miasta (na przykładzie Gostynina) - Bagrowska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
This article is a study of lexical material collected in a survey conducted among those residents of a small town, who are at least 60 years old, originate from the countryside, but have been living in Gostynin for at least 20 years and finished their education on primary school. Under analysis there are issues discussing these peoples’ vocabulary with reference to local dialects and literary language (sociolinguistic and lexicographies aspects), and the problems connected with geography of dialectic vocabulary of Gostynin residents, living on the boundaries of different dialectic regions. Integration of local dialects and literary Polish language causes dialects to fade, but further analysis proves this process to be dependant on several social factors. There are also many other problems connected with adoption of the literary language by the examined group of people. As a result, dialects tend to survive in the small town environment. The author of this article also discusses relationship between individual words selected for this study and the vocabulary of different regions. The study proved the enrichment of the dilect vocabulary taking place due to language contact of adjacent regions. Words adopted from other dialects should be treated as culture borrowing, and not as a symptom of a new dialect formation. As we all know, vocabulary does not determine the classification of language variety.